ABDIMUDA INSTAGRAM MESSAGE STRATEGY IN BUILDING ASN BRAND ENGAGEMENT - Rahadian, Fadli; H.I, Rahman (IJOSMAS, 2023)
Advances in technology and information Mixed increasing sophistication devices produced by the industry today are like bringing the world in hand. Media accessibility has become one of the most important needs of everyone due to the need for information, entertainment, education and access to information from different parts of the world. One form of technological progress that is very close to human life today is the internet network. The presence of the internet network also influences the emergence on social media. One of the most popular today is Instagram because it allows users to share short messages and information in the form of informative images or short videos. Instagram has been downloaded over a billion times and has 700 million monthly active users. Companies large and small in different industries must adapt to different technologies, especially when they use new media to inform audience. The purpose of this study is to analyze which are the priority factors of young employees to develop a strategy for the Instagram posts of young people to build ASN brand engagement.This type of research is descriptive qualitative and the method used is a case study with a constructivist paradigm. data collection techniques obtained for this study were: Primary data: in-depth interviews and secondary data: literature review (documentation). The method to verify the correctness of the data is triangulation (source and method). The first result of this study is that the social media digital management of Abdimuda Indonesia Instagram applies the message strategy method considering message composition, including message code, message material and message form.